Politeness Strategies in Master Ceremony Coaching Clinic: Comparison among Mentors and Mentees - Muhid, Abdul; Syarifaturrahman, Wahyu Kamil; Suhendra, Erwin; Alawiyah, Rosidah; Arniati, Fitri (LPPM Universitas Bumigora Mataram, 2024)
This research scrutinizes the strategy of politeness employed by Mentors (MTRs) and Mentees (MNTs) during the coaching clinic providing Master Ceremony (MC) at Universitas Bumigora. Researchers implemented some techniques (participative observation, interviews, audio recording, case studies, and focus group discussions) to monitor the interaction among the MTRs and MNTs during interaction and comprehend how the theory used, and the strategies affect the communication and lead to effectiveness of rehearsals. This research applied a descriptive qualitative method to see the natural phenomenon of data in the field. The face-saving strategy was found to be mostly applied during coaching; MTRs do 69.23% of the time, and MNTs do 80%. While the face-threatening acts, MTRs uttered 30.77%, and 20% of utterances were uttered by MNTs. Using saving strategies during coaching helps the MTRs maintain good relationships with the MNTs. This research also suggests that implementing politeness strategies creates good communication and relationships at hand. The newness of current research lies in the in-depth analysis of the politeness strategy among mentors and mentees, which the face-saving strategy significantly contributes toward communication effectiveness.